Evidence for Quinol Oxidation Activity of ImoA, a Novel NapC/NirT Family Protein from the Neutrophilic Fe(II)-Oxidizing Bacterium Sideroxydans lithotrophicus ES-1 - Jain, Abhiney; Coelho, Anaísa; Madjarov, Joana; Paquete, Catarina M.; Gralnick, Jeffrey A. (mBio, 2022)
Fe(II)-oxidizing bacteria play an important role in biogeochemical cycles. At circumneutral pH, these organisms perform extracellular electron transfer, taking up electrons from Fe(II) outside the cell, potentially through a porin-cytochrome complex in the outer membrane encoded by the Mto pathway. Sideroxydans species are important chemolithoautotrophic Fe(II)-oxidizing bacteria in freshwater environments and play a role in biogeochemical cycling of multiple elements. Due to difficulties in laboratory cultivation and genetic intractability, the electron transport proteins required for the growth and survival of this organism remain understudied. In Sideroxydans lithotrophicus ES-1, it is proposed that the Mto pathway transfers electrons from extracellular Fe(II) oxidation across the periplasm to an inner membrane NapC/NirT family protein encoded by Slit_2495 to reduce the quinone pool. Based on sequence similarity, Slit_2495 has been putatively called CymA, a NapC/NirT family protein which in Shewanella oneidensis MR-1 oxidizes the quinol pool during anaerobic respiration of a wide range of substrates. However, our phylogenetic analysis using the alignment of different NapC/NirT family proteins shows that Slit_2495 clusters closer to NirT sequences than to CymA. We propose the name ImoA (inner membrane oxidoreductase) for Slit_2495. Our data demonstrate that ImoA can oxidize quinol pools in the inner membrane and is able to functionally replace CymA in S. oneidensis . The ability of ImoA to oxidize quinol in vivo as opposed to its proposed function of reducing quinone raises questions about the directionality and/or reversibility of electron flow through the Mto pathway in S. lithotrophicus . IMPORTANCE Fe(II)-oxidizing bacteria play an important role in biogeochemical cycles. At circumneutral pH, these organisms perform extracellular electron transfer, taking up electrons from Fe(II) outside the cell, potentially through a porin-cytochrome complex in the outer membrane encoded by the Mto pathway. Electrons from Fe(II) oxidation would then be transported to the quinone pool in the inner membrane via periplasmic and inner membrane electron transfer proteins. Directly demonstrating the functionality of genes in neutrophilic iron oxidizers is challenging due to the absence of robust genetic methods. Here, we heterologously expressed a NapC/NirT family tetraheme cytochrome ImoA, encoded by Slit_2495 , an inner membrane protein from the Gram-negative Fe(II)-oxidizing bacterium Sideroxydans lithotrophicus ES-1, proposed to be involved in extracellular electron transfer to reduce the quinone pool. ImoA functionally replaced the inner membrane c -type cytochrome CymA in the Fe(III)-reducing bacterium Shewanella oneidensis . We suggest that ImoA may function primarily to oxidize quinol in S. lithotrophicus .